Signing Up for Multiple Truths: (Re)telling Who we are as Racialized Canadians and Indigenous Peoples in Relation to Each Other - Khan, Momina; Pushor, Debbie (Critical Education, 2023)
By using autobiographical narrative inquiry (Clandinin & Connelly, 2000) and poetry (Leggo, 1998), we share the story of a Muslim Canadian female graduate student, as experienced by the student and her graduate supervisor. We unpack an email expressing concern, written by an Indigenous male student about the work of the Muslim female student to her supervisor, during their Master’s coursework. We work through layers of mis/understandings and a shared desire to stand together in a relationship connecting our unique beings. Our intent is to emphasize the importance of magnifying our human existence and universal dignity beyond binaries by making more space for one another, by listening harder and longer, by learning with open and vulnerable hearts, and by considering what work each of us can do, individually and collectively, to decrease the foreignness, first among ourselves and then among racialized, Indigenous, and white settler Canadians.